Problems of humanitarian mine clearing - Shchecunov В. В.; Yukhin А. Н. (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
Problems of humanitarian mine clearing were considered. System of specialists training on mine clearing in the frame of international collaboration was revealed. New undetonating ways of neutralization VOP and equipment for their realization were shown.